Strategies for optimising TB-HIV co-treatment in children and adolescents with drug-susceptible tuberculosis on rifampicin-based standard regimens - Chabala, Chishala (Department of Medicine, 2025)
Children with HIV are highly susceptible to tuberculosis (TB) and often require concurrent antiretroviral treatment (ART) and antituberculosis therapy. However, rifamycins, the key drugs for TB treatment, significantly interact with many ART classes, necessitating adjustments to one or both therapies. In African and other low-resource settings, modifications typically involve ART regimens due to constrained drug options. This thesis presents four pharmacokinetics and one clinical study evaluating strategies for HIV/TB co-treatment in children and adolescents receiving rifampicin-based TB therapy, nested within two clinical trials across four African countries. First, we assessed the World Health Organization's (WHO) weight-band dosing recommendations for first-line TB drugs using fixed-dose combination tablets. Next, we examined two dose-adjustment strategies involving lopinavir/ritonavir, a widely available protease inhibitor for first- and second -line ART, using both liquid and tablet formulations. We then investigated a twice-daily dosing regimen of tenofovir alafenamide for children co-treated with rifampicin. Lastly, we evaluated clinical outcomes in children with HIV/TB and non-severe TB who received standard antituberculosis dosing. Our findings show that while WHO revised dosing guidelines improve TB drug exposure in children, target levels are not consistently achieved across weight bands; children in the lowest and highest weight categories experience lower exposures compared to adult reference targets. For dose modification, the use of modified 8-hourly lopinavir/ritonavir liquid in younger children was ineffective, whereas double-dosing with tablet formulations provided adequate exposures in older children and adolescents, countering rifampicin's effects. Twice-daily tenofovir alafenamide dosing counteracts rifampicin's inducing effects but requires caution when administered with adjusted protease inhibitor doses. Finally, we found that children with HIV/TB who were treated for non-severe TB had worse treatment outcomes compared to their HIV- uninfected counterparts, but they could also receive a shorter antituberculosis treatment as the duration of treatment did not impact their tuberculosis outcomes. In summary, optimizing HIV/TB co-treatment for children is a constantly evolving area that must adapt to advances in both HIV and TB care. This research will contribute to the understanding of strategies that can be used to optimise the treatment of children living with HIV/TB for improved clinical outcomes.